A genome‐wide association study for a proxy of intermuscular fat level in the Italian Large White breed identifies genomic regions affecting an important quality parameter for dry‐cured hams. (3rd February 2017) - Fontanesi, L.; Schiavo, G.; Galimberti, G.; Bovo, S.; Russo, V.; Gallo, M.; Buttazzoni, L.
Summary: Intermuscular fat content in protected designations of origin dry‐cured hams is a very important meat quality trait that affects the acceptability of the product by the consumers. An excess in intermuscular fat (defined as the level of fat deposition between leg muscles) is a defect that depreciates the final product. In this study we carried out a genome‐wide association study for visible intermuscular fat (VIF) of hams in the Italian Large White pig breed. This trait was evaluated on the exposed muscles of green legs in 1122 performance‐tested gilts by trained personnel, according to a classification scale useful for routine and cheap evaluation. All animals were genotyped with the Illumina PorcineSNP60 BeadChip. The genome‐wide association study identified three QTL regions on porcine chromosome 1 (SSC1; accounting for 79% of the SNPs below the 5.0E−04 threshold) and SSC2, two on SSC7 and one each on SSC3, SSC6, SSC9, SSC11, SSC13, SSC15, SSC16 and SSC17. The most significant SNP ( ALGA0004143 on SSC1 at 77.3 Mb; P FDR < 0.05), included in the largest QTL region which spanned about 6.8 Mb on SSC1, is located within the glutamate ionotropic receptor kainate type subunit 2 ( GRIK2 ) gene. Functional annotation of all genes included in QTL regions for VIF suggested that intermuscular fat in the Italian Large White breed is a complex trait apparently influenced by complex biological mechanisms also involving obesity‐related processes. These QTL target mainly chromosome regions different from those affecting subcutaneous and intramuscular fat deposition.